Principal’s Strategies in Implementing Digital Literacy - Rana Arisma Valeves; Tri Widayatsih; Mahasir Mahasir (Journal of Social Work and Science Education, 2026)
This study aims to analyze the principal’s strategies in implementing digital literacy at SMK Negeri 1 Sekayu, Indonesia, focusing on planning, implementation, and supervision, as well as associated challenges and solutions. Employing a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving the principal, vice principals, teachers, and educational staff. Data analysis followed an interactive model of reduction, display, and conclusion drawing. The findings reveal a multi-stage strategy. Planning involved integrating digital literacy into the curriculum and annual programs, developing technology-based instructional tools, and providing supporting facilities. Implementation centered on encouraging digital learning platforms, conducting professional development workshops to enhance teachers’ digital competencies, and promoting project-based learning with digital technology. Supervision was executed through regular monitoring and evaluation of classroom practices. Key challenges identified include suboptimal platform use, varying teacher digital competence, and infrastructure limitations. Solutions implemented involve strengthening teacher capacity through continuous training and optimizing available technological resources. The novelty of this study lies in its specific examination of leadership strategies for digital literacy within a vocational high school context in Indonesia, offering insights into the principal’s role as a central driver. Practically, the findings provide a strategic framework for school leaders in similar contexts to navigate digital integration. This study contributes to educational leadership literature by demonstrating that effective digital literacy implementation requires coherent, multi-level strategies from planning through to supervision, coupled with targeted solutions to address persistent challenges.